New realities in audio a practical guide for VR, AR, MR, and 360 video - Schutze, Stephan; Irwin-Schutze, Anna (CRC Press, Taylor & Francis Group, 2018)
Virtual and Augmented realities and 360 video technologies are rapidly entering our homes and office spaces. Good quality audio has always been important to the user experience, but in the new realities, it is more than important, it's essential. This practical guide helps you navigate the challenges and pitfalls of designing audio for these new realities. This technology is different from anything we've seen before and requires an entirely new approach; this book will introduce the broad concepts you need to know before delving into the practical detail you need.